h y Hyug Baeg Im. - Im, Hyug Baeg.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Palgrave Macmillan, 2020)
This is a perfect one-country study: deeply engaged in the theoretical and comparative literature, intimately informed about South Korean history, bringing to bear some unknown aspects of the case. A major contribution to studies of authoritarianism and of transitions to democracy. $1 (BAdam Przeworski, Carroll and Milton Petrie Professor Emeritus, Department of Politics, New York University, USA This book analyses democratization and democracy in South Korea since 1960. The book starts with an analysis of the distinctive characteristics of bureaucratic authoritarianism and how democratic transition had been possible after inconclusive and protracted (3z(Btug of war(3y (Bbetween authoritarian regime and democratic opposition. It then goes on to explore what the opportunities and constraints to the new democracy are to be a consolidated democracy, how new democracy had changed the industrial relations in the post-transition period, how premodern political culture such as Confucian patrimonialism and familism had obstructed democratic consolidation, and the improvement of quality of democracy. The author compares empirically, from the perspective of a comparative political scientist, political regime superiority of democracy over authoritarianism with regard to economic development. He concludes that (3z(Bdemocratic incompetence(3y (Btheory has been proven wrong and, in South Korea, democracy has performed better than authoritarian regimes in terms of economic growth with equity, employment, distribution of income, trade balance, and inflation. This book will benefit political scientists, development economists, labor economists, religious sociologists, military sociologists, and historians focusing on East Asian history. Hyug Baeg Im is a professor emeritus at Korea University and a chaired professor at GIST. He received his M.A. and Ph.D. from the University of Chicago, USA. He served as an EC member of IPSA and received ROK National Academy of Sciences Prize. Prof. Im's recent publications includeThe Possibility of Peace in the Korean Peninsula (2017) and Mongering North Korean Democracy for Inter-Korean Peace (2015).s
1. Introduction: My democratization studies in retrospect -- 2. The rise of bureaucratic authoritarianism in South Korea -- 3. Recasting Park Chung Hee's authoritarianism: myths, reality, and legacies -- 4. Politics of democratic transition from authoritarian rule in South Korea -- 5. Christian churches and democratization in South Korea -- 6. Democratic consolidation in South Korea: opportunities and constraints -- 7. From affiliation to association: the challenge of democratic consolidation in Korean industrial relations -- 8. Faltering democratic consolidation: democracy at the end of the Three Kims era -- 9. The development and change of Korean democracy since democratic transition in 1987: Three Kims Politics and after -- 10. Democratic development and authoritarian development compared -- 11. Better democracy, better economic growth?.
Keywords: Asia$1 (BPolitics and government.s; Democracy; Korea$1 (BHistory.s; Asian Politics; Democracy; History of Korea